The Effects of Modified Games on the Development of Gross Motor Skill in Preschoolers - Indah Lestari; Tri Ratnaningsih (International Journal of Evaluation and Research in Education (IJERE), 2016)
Gross motor skills on children must be optimized much earlier since it plays important role not only on their interaction process but also in supporting other multiple developments. One of the means in developing child's motor skill is by providing innovative games i.e. modified games including game format, game timing, and game sequence. The objective of this research was to prove the effects of modified games to the development of gross motor skill of preschoolers. Research method was pre-experimental with One Group Pre-post test Design approach. Research samples were the students of Group B Kindergarten in the districts of Gedeg as many as 180 students which were conducted by using purposive sampling. Research instrument was observation during one month. The data was analyzed by Wilcoxon sign rank test. The results suggested that there was effect of modified games to the development of preschool gross motor skill with p-value = 0.000. Changes on motor skill development were obtained from those who were initially on the beginning stage, as many as 101 respondents, became 14 respondents after intervention. Development stage proceeded as expected, from initial 65 respondents the number increased to 130 respondents. At the end of the intervention, there were even 36 respondents whose development stage beyond where they were supposed to be. This proved that the provision of modified games had positive effects on physical, cognitive, and social development. Modified games triggered children's interest and made them be willing to train their activities as well as muscle development, decreased saturation, and improved their skills in a fun way.